Usability perception of joysticks for self-proplled agricultural equipment with cabin: a study of the ergonomic design (Human Factors in Design, 2023)
The joystick is one of the main interaction interfaces for use in farming equipment and self-propelled vehicles, whose purpose involves the execution of functional operations. Their designs vary according to the equipment and can influence the use interaction. The present study aimed to evaluate the influence of the design of these joysticks on usability perception. The exploratory methodological procedures involved a simulated activity evaluation with perception protocols. The results indicate that the design of the joysticks has a strong influence on the perception of usability and that the protocols employed can assist in studies on the Ergonomic Design of these interfaces.
Keywords: joystick; agricultural equipment; perceived comfort; usability